2012
DOI: 10.1029/2012gc004357
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on the provenance of the ANDRILL AND‐2A succession (western Ross Sea, Antarctica) from apatite triple dating

Abstract: Apatite triple dating (fission track, U‐Pb and U‐Th/He techniques) has been applied to detrital grains from the sedimentary core drilled during the ANDRILL 2A project, which documents the Miocene history of the Victoria Land Basin (western Ross Sea). High‐temperature cooling ages show two main clusters (about 30 and 500 Ma) whereas most of low‐temperature data are late Oligocene‐Early Miocene in age. These latter data are related to the exhumation of the Transantarctic Mountains south of the Discovery Accommod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 82 publications
2
34
0
Order By: Relevance
“…The McMVG, which surrounds the McMurdo Sound and VLB Basins, consists of several large alkaline stratovolcanoes associated with the West Antarctic rift system (Gunn & Warren, 1962;Kyle, 1990; Figure 1). Eruptions began in the late Oligocene (~26 Ma; Sandroni & Talarico, 2004;Smellie, 2000;Zattin et al, 2012) and became more frequent after~20 Ma (Di Vincenzo et al, 2010). Mount Morning is the only known source of early to middle Miocene volcanic material recovered from AND-2A core (Di Roberto et al, Vincenzo et al, 2010;Nyland et al, 2013).…”
Section: Location and Geological Settingmentioning
confidence: 99%
“…The McMVG, which surrounds the McMurdo Sound and VLB Basins, consists of several large alkaline stratovolcanoes associated with the West Antarctic rift system (Gunn & Warren, 1962;Kyle, 1990; Figure 1). Eruptions began in the late Oligocene (~26 Ma; Sandroni & Talarico, 2004;Smellie, 2000;Zattin et al, 2012) and became more frequent after~20 Ma (Di Vincenzo et al, 2010). Mount Morning is the only known source of early to middle Miocene volcanic material recovered from AND-2A core (Di Roberto et al, Vincenzo et al, 2010;Nyland et al, 2013).…”
Section: Location and Geological Settingmentioning
confidence: 99%
“…() mainly discussed the tectonic implications of this young erosional event, no climate implication on WAIS dynamics has been investigated. In the ANDRILL cores (Talarico et al ., ; Zattin et al ., , ; Sandroni and Talarico, ) fission‐track analysis of detrital apatites coupled with sedimentary clasts analysis was used to reconstruct the Miocene glacial flows. These studies revealed a syn‐sedimentary volcanic origin for most young FT apatites (pre‐McMurdo Eocene volcanic event, Zattin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for unknown grains yielding Mesozoic or older ages, 207 Pb-corrected age uncertainties either >25% or >100 Ma at the 2r level were thus excluded from single-grain age-plots (though not from Tera Wasserburg). This approach is ultimately arbitrary, but is similar to previously published approaches used in Zattin et al (2012), Mark et al (2016), andO'Sullivan et al (2016). This method is unsatisfactory for very young grains, however, as a given fixed age uncertainty as a percentage of the total age approaches infinity as the age of grains approaches 0 Ma.…”
Section: Single Grain La-icp-ms Analysesmentioning
confidence: 97%
“…U-Pb Dating of Detrital Apatite by LA-ICPMS Due to advances in LA-ICP-MS data reduction and matrix-matched standards, it is now possible to accurately, precisely and rapidly date apatite grains containing appreciable common-Pb by U-Pb geochronology (e.g., Chew et al 2014;Thomson et al 2012). This has led to a number of provenance studies employing the apatite U-Pb system in recent years (e.g., Carrapa et al, 2009;Mark et al, 2016;O'Sullivan et al, 2016;Zattin et al, 2012).…”
Section: Why Study the River Tarn?mentioning
confidence: 99%
See 1 more Smart Citation